Penguatan Peran Otoritas Jasa Keuangan Dalam Perlindungan Hukum Bagi Industri Jasa Keuangan dan Masyarakat Pasca Berlakunya Undang-Undang No. 4 Tahun 2023 Tentang Pengembangan Dan Penguatan Sektor Keuangan - Yustisia Nasution, Arjanggi (UNES Law Review, 2024)
Strengthening of the role of OJK after the enactment of the P2SK Law, where after the enactment of the P2SK Law there was a regulation that all actions including decisions taken by the OJK based on the P2SK Law were not objects of lawsuits that could be submitted to the state administrative court. Of course, this will have a direct impact on the financial services industry and society if OJK's actions and decisions have a negative impact on them. Furthermore, the emergence of a new institution, namely the OJK Supervision Body which functions to assist the DPR in carrying out its oversight function as well as improving the performance, accountability, independence, transparency, and institutional credibility of the OJK. This paper aims to provide a better understanding of legal protection for the financial services industry and the public in the context of their relationship with the OJK after the enactment of the P2SK Law.